2013
DOI: 10.4028/www.scientific.net/amm.415.510
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Methodologies Used for Fault Diagnosis of Gearbox

Abstract: A review of methods used for fault recognition of the rolling elements in gearbox, namely gear and bearing, is presented in this paper. The procedure of the fault recognition can be classified into three phases, which are data acquisition, data processing or important features extraction, and the fault mode detection. Many different methods have been developed in dealing with each phase, so that the arrangement of the entire process has different strategies. This paper summarizes some general used and recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…But this process is not an easy task. The first step of fault diagnosis for most mechanical equipment is signal acquisition [26]. The vibration signal collected by contact accelerometer and the acoustic signal collected by non-contact microphone are both not just the working signal of gear.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…But this process is not an easy task. The first step of fault diagnosis for most mechanical equipment is signal acquisition [26]. The vibration signal collected by contact accelerometer and the acoustic signal collected by non-contact microphone are both not just the working signal of gear.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In fact, in [17], we already pointed out the possibility of overcoming limits related to bearing fault diagnosis under non-stationary conditions using MTA instead of MCSA. Furthermore, in [18], a review regarding the detection and diagnosis methodologies for gearboxes, it is demonstrated that the most useful signals for diagnosis are currents, torques, or vibrations. Since the manipulators' joints are composed of electric drives and speed reducers also for these cobots, the same considerations above may be considered valid.…”
Section: Related Workmentioning
confidence: 99%